INTEGRATING HYPERCONTENT INTO E-MODULES FOR READING COMPREHENSION TO ENHANCE NEWS LITERACY AMONG HIGH SCHOOL STUDENTS - Khotimah, Khusnul; Atmazaki, Atmazaki (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Purpose: This study aims to develop a hypercontent-based e-module to improve reading comprehension skills of news texts in grade XI students at the UNP Laboratory Development Senior High School. Method: The research uses the 4D development model (Define, Design, Develop, Disseminate) to produce interactive and adaptive teaching materials. Result: In the Define stage, the analysis revealed that students face difficulties in understanding news text material and have not utilized technology in the learning process. In the Design stage, the developed e-module was designed according to the curriculum, engaging, and integrated with various digital resources. In the Develop stage, the e-module was validated by content, language, and design experts with a score of 84.29%, indicating very high validity. Conclusion: The practicality tests by teachers and students also showed highly practical results, with scores of 98% and 85.95%, respectively. Based on these results, the e-module is considered feasible and effective for use in teaching. Implication: The implications of this study are that the hypercontent-based e-module can enhance students' reading comprehension skills and support more interactive learning while utilizing technology in education.